A nomogram for individually predicting overall survival for elderly patients with early breast cancer: a consecutive cohort study - Zhong, Ying; Zhou, Yidong; Xu, Yali; Wang, Zhe; Mao, Feng; Shen, Songjie; Lin, Yan; Sun, Qiang; Sun, Kai (Frontiers in Oncology, 2023)
BACKGROUND: Elderly patients with breast cancer are highly heterogeneous, and tumor load and comorbidities affect patient prognosis. Prediction models can help clinicians to implement tailored treatment plans for elderly patients with breast cancer. This study aimed to establish a prediction model for breast cancer, including comorbidities and tumor characteristics, in elderly patients with breast cancer. METHODS: All patients were ≥65 years old and admitted to the Peking Union Medical College Hospital. The clinical and pathological characteristics, recurrence, and death were observed. Overall survival (OS) was analyzed using the Kaplan–Meier curve and a prediction model was constructed using Cox proportional hazards model regression. The discriminative ability and calibration of the nomograms for predicting OS were tested using concordance (C)-statistics and calibration plots. Clinical utility was demonstrated using decision curve analysis (DCA). RESULTS: Based on 2231 patients, the 5- and 10-year OS was 91.3% and 78.4%, respectively. We constructed an OS prediction nomogram for elderly patients with early breast cancer (PEEBC). The C-index for OS in PEEBC in the training and validation cohorts were 0.805 and 0.746, respectively. Calibration of the nomogram revealed a good predictive capability, as indicated by the calibration plot. DCA demonstrated that our model is clinically useful. CONCLUSIONS: The nomogram accurately predicted the 3-year, 5-year, 10-year OS in elderly patients with early breast cancer.